MODEL ARIMA BOX-JENKINS UNTUK MERAMALKAN JUMLAH KUNJUNGAN WISATAWAN MANCANEGARA DI KABUPATEN LOMBOK BARAT - Rifani Nur Sindy Setiawan; Wirajaya Kusuma; Gilang Primajati; Siti Soraya; Istin Fitriana Aziza (JURNAL AGRIMANSION, 2023)
The development of tourism in West Lombok is supported by geographical conditions with scattered clusters of small islands (gili), tropical climate, and the cultural peculiarities of the Sasak tribe, so that it becomes an attraction in the development of global tourist destinations. West Lombok tourism development will be even more attractive with the establishment of the Mandalika National Tourism Development Strategic Area. West Lombok can play a role concurrently with this strategic policy momentum. Developing new growth centers based on the tourism sector in collaboration with other sectors and packaging the village's potential to become a thematic tourism village. Methods for predicting the number of tourist visits to West Lombok Regency are urgently needed to assist the district government in preparing appropriate facilities and infrastructure if there is a possibility of an increase in tourist visits. The method used in this study is the Box-Jenkins ARIMA method to predict the number of foreign tourist visits in West Lombok Regency. The data used in this study is secondary data sourced from the West Lombok Regency Tourism Office from January 2014 to December 2021. The results showed that the ARIMA model (2,1,2) is the most suitable model for predicting the number of foreign tourist visits to West Lombok Regency because this model produces the smallest Sum of Squared Errors (SSE) and Mean Squared Error (MSE) values compared to other models.